Decomposition of leaf litter mixtures across biomes: The role of litter identity, diversity and soil fauna. (28th July 2020) - Zhou, Shixing; Butenschoen, Olaf; Barantal, Sandra; Handa, Ira Tanya; Makkonen, Marika; Vos, Veronique; Aerts, Rien; Berg, Matty P.; McKie, Brendan; Van Ruijven, Jasper; Hättenschwiler, Stephan; Scheu, Stefan
Abstract: At broad spatial scales, the factors regulating litter decomposition remain ambiguous, with the understanding of these factors largely based on studies investigating site‐specific single litter species, whereas studies using multi litter species mixtures across sites are rare. We exposed in microcosms containing single species and all possible mixtures of four leaf litter species differing widely in initial chemical and physical characteristics from a temperate forest to the climatic conditions of four different forests across the Northern Hemisphere for 1 year. Calcium, magnesium and condensed tannins predicted litter mass loss of single litter species and mixtures across forest types and biomes, regardless of species richness and microarthropod presence. However, relative mixture effects differed among forest types and varied with the access to the litter by microarthropods. Access to the microcosms by microarthropods modified the decomposition of individual litter species within mixtures, which differed among forest types independent of litter species richness and composition of litter mixtures. However, soil microarthropods generally only little affected litter decomposition. Synthesis . We conclude that litter identity is the dominant driver of decomposition across different forest types and the non‐additive litter mixture effects vary among biomes despite identical leaf litter chemistry. These results suggest that across large spatial scales the environmental context of decomposing litter mixtures, including microarthropod communities, determine the decomposition of litter mixtures besides strong litter trait‐based effects. Abstract : We conclude that litter identity is the dominant driver of decomposition across different forest types and the non‐additive litter mixture effects vary among biomes despite identical leaf litter chemistry. These results suggest that across large spatial scales the environmental context of decomposing litter mixtures, including microarthropod communities, determine the decomposition of litter mixtures besides strong litter trait‐based effects.